Technomilitary Fantasy in the 1980s. Issue 2 (June 2015) - Andrews, Chad
<x content-type="archive" xml:space="preserve">Abstract</x> In America in the 1980s, a group of sf authors played a role in the development of influential policies and technologies, including Ronald Reagan's Strategic Defense Initiative (SDI). Guided by writers such as Jerry Pournelle and Larry Niven, they formed an advocacy group, the Citizens Advisory Council on National Space Policy, in order to undermine the Cold War policy of "mutually assured destruction" (MAD) and support the development of new technologies capable of "weaponizing space" as a means to protect the American homeland. While their political involvements have been explored in some detail elsewhere, this article aims to outline the discursive formation their various fictions helped generate—a formation I term "technomilitary fantasy"—and argues that their contributions as writers and editors of military sf, particularly with the series of anthologies There Will Be War (1983-1990), helped define a popular way of imagining technology in that period. That concept can be called "instrumentalism, " and it played a key role in the social and political texture of 1980s America.